Efficacy of Shatavari gopakanyadi decoction in management of Polon visha (Viper envenomation): A conceptual review: Palathiratne S.M.1*, Kulatunga W.M.S.S.K.2 and Jayawardana H.G.G.3 (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2024)
Polon visha (viper envenomation) is an important area of focus in the traditional Sarpa visha vedakama (snake-venom treatment system) of Sri Lankan indigenous medicine. Polon kulaya according to Sri Lankan indigenous medicine comprises of many varieties of vipers. Polon kulaya of Sri Lankan indigenous medicine can be correlated to Mandalika type of snakes mentioned in Ayurveda and also to Viperidae family of snakes of modern science. Shatavari gopakanyadi decoction is a unique Kashaya drug of Sri Lankan indigenous medicine, primarily indicated in the management of Raktapitta and Raktapradara; yet to date any published research work about this particular decoction or its utility in treatment of viper envenomation, is unavailable. The objective of this review research was to conceptually validate the efficacy of Shatavari gopakanyadi kashaya in the management of Polon visha envenomation. For this purpose; principal manuscripts of Sri Lankan indigenous medicine, key compendiums of Ayurveda, relevant textbooks of modern science and published research articles were extensively reviewed and analyzed. The antagonisms of the overall pharmacological actions of Shatavari gopakanyadi kashaya against Dosha dushya tatwa of Polon visha envenomation were highlighted. Shatavari gopakanyadi kashaya possess Pitta shamaka, Rakta shamaka, Rakta stambhana, Vishaghna and Vrimhana karma as primary pharmacological actions; which indeed are directly antagonistic to the pathophysiology and Dosha dushya tatwa of Polon visha envenomation. The accessory pharmacological actions of Shatavari gopakanyadi kashaya are Daha prashamana, Varnya, Trishna nigrahana, Angamarda prashamana and Jwarahara. These actions are also beneficial in the treatment of Polon visha envenomation according to case specific suitability and oppose its clinical features. In a Nutshell, thus the efficacy of Shatavari gopakanyadi decoction in management of Polon visha (viper envenomation) is conceptually validated conclusively as per fundamentals of Ayurveda and Sri Lankan indigenous medicine.